ANALYSIS OF SUB-GRID MODELING EFFECTS IN THE SIMULATION OF THE SINGLE-PHASE TURBULENT FLOW IN AN INDUSTRIAL CYCLONE SEPARATOR - Salvo, R. V.; Souza, F. J.; Martins, D. A. M. (Revista de Engenharia Térmica, 2012)
In the present work two turbulence modeling approaches, namely Large Eddy Simulation and Detached Eddy Simulation, are employed to predict turbulent, swirling flow within an industrial cyclone separator running at Reynolds number 267,000. The results from three LES models, Smagorinsky, dynamic and Yakhot, and the SST-DES model of Strelets have been compared to experimental results for the average axial and tangential velocities. The Navier-Stokes solver is based on an unstructured, finite volume, cell-centered algorithm such that the details of the geometry can be accurately represented. Based on the comparison with the experimental results, it has been found that the Yakhot model provides the most accurate predictions for the tangential velocities, whereas the dynamic LES and the Smagorinsky models overpredict it and the SST-DES model underpredicts it. However, the conclusions are different regarding the axial velocity. Implications of the turbulence modeling for the particle separation are discussed.